Analisis Perbedaan Sistem Perbankan Konvensional dan Perbankan Syariah Dalam Sistem Perbankan Indonesia - Hidayah, Nur; B, Baidhowi; Novita, Yustina Dhian (Media Hukum Indonesia (MHI), 2025)
This article analyzes the differences between conventional banking and Islamic banking systems in Indonesia, focusing on their operational principles and products. Indonesia, as a country with a large population and a Muslim majority, has two banking systems, namely conventional banking and Islamic banking. This article aims to provide a better understanding of these two banking systems and their implications for the development of an inclusive and sustainable financial system in Indonesia.